Circularly polarized-thermally activated delayed fluorescent materials based on chiral bicarbazole donors. Issue 45 (18th May 2022) - Poulard, Laurélie; Kasemthaveechok, Sitthichok; Coehlo, Max; Kumar, Ramar Arun; Frédéric, Lucas; Sumsalee, Patthira; d'Anfray, Timothée; Wu, Sen; Wang, Jingxiang; Matulaitis, Tomas; Crassous, Jeanne; Zysman-Colman, Eli; et al.
Abstract : We describe a molecular design to generate circularly polarized thermally activated delayed fluorescence emitters in which chiral bicarbazole donors are connected to acceptor units via a rigid 8-membered cycle. Abstract : We describe herein a molecular design to generate circularly polarized thermally activated delayed fluorescence emitters in which chiral bicarbazole donors are connected to acceptor units via a rigid 8-membered cycle and how the nature of the donor and acceptor units affect the photophysical and chiroptical properties.